2015
DOI: 10.7150/thno.11607
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Retrograde Coronary Venous Infusion of Basic Fibroblast Growth Factor Enhances Engraftment and Differentiation of Bone Marrow Mesenchymal Stem Cells for Cardiac Repair after Myocardial Infarction

Abstract: Aim: Basic fibroblast growth factor (bFGF) increases the migration and viability of bone marrow mesenchymal stem cells (MSCs) in vitro. Retrograde coronary venous infusion can provide both increased regional bFGF concentrations and homogeneous cell dissemination. We determined whether retrograde delivery of bFGF enhances the potency of transplanted MSCs for cardiac repair in a canine infarct model.Methods and Results: Under hypoxic conditions, cellular migration was significantly increased in MSCs co-cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Having mentioned this, the combined effect of BM-MSCs along with basic fibroblast growth factor ( bFGF )-binding ECM has been observed to improve the left ventricular (LV) function and enhance myocardial regeneration [ 69 ]. One of the most effective delivery methods for the treatment has been observed to be via the retrograde infusion of the two [ 70 ]. Mixed treatment of BM-MSCs with endothelial progenitor cells (EPCs) pre-treated with salvianolic acid B results in reduced infarct area and enhanced stem cell proliferation [ 71 ].…”
Section: Main Textmentioning
confidence: 99%
“…Having mentioned this, the combined effect of BM-MSCs along with basic fibroblast growth factor ( bFGF )-binding ECM has been observed to improve the left ventricular (LV) function and enhance myocardial regeneration [ 69 ]. One of the most effective delivery methods for the treatment has been observed to be via the retrograde infusion of the two [ 70 ]. Mixed treatment of BM-MSCs with endothelial progenitor cells (EPCs) pre-treated with salvianolic acid B results in reduced infarct area and enhanced stem cell proliferation [ 71 ].…”
Section: Main Textmentioning
confidence: 99%
“…Because of their many advantages, such as ease of isolation and culture, their directional migration and lack of immune rejection, MSCs are considered to have great therapeutic potential for many diseases . Injection of MSCs has been utilized to alleviate atherosclerosis, myocardial ischaemia and vascular balloon injury . Experiments have shown that oxidative stress exists in vascular intima and the blood circulation following both vein grafting and vascular injury, after a short period of time and lasting for several weeks .…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 may stimulate the proliferation of mesenchymal stem cells and induce their differentiation into osteoblasts 33, 34; the low concentration of TGF-β1 promotes the maturation of osteoclasts 35. These process couple bone resorption with bone formation 26, 36, 37.…”
Section: Discussionmentioning
confidence: 99%